2022
DOI: 10.7717/peerj.12914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interaction between occupational stress and polymorphisms of MTHFR gene and SELE gene on hypertension

Abstract: Background Gene-environment interaction is related to the prevalence of hypertension, but the impact of genetic polymorphisms on hypertension may vary due to different geography and population. Objective To explore the impact of the interaction among occupational stress and MTHFR gene and SELE gene polymorphism on the prevalence of hypertension in Xinjiang oil workers. Methods A case-control study was conducted on 310 oil workers. In an oilfield base in Karamay City, Xinjiang, 155 hypertensive patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several approaches have been developed to target E-selectin, including monoclonal antibodies and small molecule inhibitors and have shown promise in preclinical studies by reducing tumor growth and metastasis [75][76][77][78][79]. SELE polymorphisms have been reported as possible risk indicators for a number of medical conditions such as hypertension in cases of occupational stress [80], risk of coronary artery disease [81], enlargement of renal cyst in patients with polycystic kidney disease [82], type 2 diabetes [83] and subclinical atherosclerosis and increased platelet activity in systemic lupus erythematosus [84]. We demonstrated that rs1534904 (T/A and T/G) could provoke important alterations in DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been developed to target E-selectin, including monoclonal antibodies and small molecule inhibitors and have shown promise in preclinical studies by reducing tumor growth and metastasis [75][76][77][78][79]. SELE polymorphisms have been reported as possible risk indicators for a number of medical conditions such as hypertension in cases of occupational stress [80], risk of coronary artery disease [81], enlargement of renal cyst in patients with polycystic kidney disease [82], type 2 diabetes [83] and subclinical atherosclerosis and increased platelet activity in systemic lupus erythematosus [84]. We demonstrated that rs1534904 (T/A and T/G) could provoke important alterations in DNA.…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR enzyme is coded by the MTHFR gene that is located on the short arm of chromosome 1 (1p36.3) and there are two isoforms in humans [13]. The first isoform is about 77 kDa protein, and the second is 70 kDa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 20th century, experimental and clinical studies have confirmed that fetal malformations are closely related to 5,10-methylenetetrahydrofolate reductase (MTHFR), folic acid (FA), and trace elements, and will affect the fetal condition of early pregnant women. [14][15][16][17][18] Genetic susceptibility genes such as the MTHFR gene may be involved in the occurrence and development of fetal malformations. [17] Based on this foundation, this article takes women in early pregnancy as the starting point to study the value and correlation of MTHFR, FA, and trace elements in preventing fetal malformations, in order to provide reference for fetal assessment during pregnancy.…”
Section: Introductionmentioning
confidence: 99%